A phase 1 study to evaluate the safety, pharmacology, and feasibility of continuous infusion nelarabine in patients with relapsed and/or refractory lymphoid malignancies. Issue 4 (29th November 2022) - Boddu, Prajwal C.; Senapati, Jayastu; Ravandi‐Kashani, Farhad; Jabbour, Elias J.; Jain, Nitin; Ayres, Mary; Chen, Yuling; Keating, Michael J.; Kantarjian, Hagop M.; Gandhi, Varsha; Kadia, Tapan M.
Abstract: Background: Nelarabine is a purine nucleoside analogue prodrug approved for the treatment of relapsed and refractory T‐cell acute lymphoblastic leukemia (R/R T‐ALL) and lymphoblastic lymphoma (T‐LBL). Although effective in R/R T‐ALL, significant neurotoxicity is dose‐limiting and such neurotoxicity associated with nucleoside analogues can be related to dosing schedule. Methods: The authors conducted a phase 1 study to evaluate the pharmacokinetics and toxicity of nelarabine administered as a continuous infusion (CI) for 5 days (120 hours), rather than the standard, short‐infusion approach. Results: Twenty‐nine patients with R/R T‐ALL/LBL or T‐cell prolymphocytic leukemia (T‐PLL) were treated, with escalating doses of nelarabine from 100 to 800 mg/m 2 /day × 5 days. The median age of the patients was 39 years (range, 14–77 years). The overall response rate was 31%, including 27% complete remission (CR) or CR with incomplete platelet recovery (CRp). Peripheral neuropathy was observed in 34% of patients, including four ≥grade 3 events related to nelarabine. Notably, there was no nelarabine‐related central neurotoxicity on study. The maximum tolerated dose was not reached. Pharmacokinetic data suggested no relationship between dose of nelarabine and accumulation of active intracellular ara‐GTP metabolite. Higher intracellular ara‐GTP concentrations were statistically associated with a favorable clinical response. Conclusion: Preliminary evaluation of continuous infusion schedule of nelarabine suggests that the safety profile is acceptable for this patient population, with clinical activity observed even at low doses and could broaden the use of nelarabine both as single agent and in combinations by potentially mitigating the risk of central nervous system toxicities. Abstract : Nelarabine administered as continuous infusion is safe and has significant clinical activity in patients with T‐cell leukemia. The continuous infusion schedule of nelarabine was not associated with central neurotoxicity in this study.